Estimating the net effects of migration and remittances on poverty and inequality: Comparison of Fiji and Tonga - Richard P. C. Brown; Eliana Jimenez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
We use original 2005 household survey data from Fiji and Tonga to estimate the impact of migration and remittances on income distribution and measures of poverty, after controlling for selectivity in migration and endogeneity in the relationship between remittances and income. Measures of inequality and poverty based on actual, with-migration income and remittances are then compared with those based on a no-migration scenario. Counterfactual household incomes are estimated, taking account of what the migrant members would have earned had they not migrated. The results are compared with alternative income estimates in which remittances are treated simplistically as exogenous transfers. The positive effects of migration and remittances on poverty alleviation and income distribution are found to be stronger when the more rigorous, counterfactual income estimates are used.
Keywords: F22; F24; I32; O15; 330; migration; remittances; income distribution; poverty; Fiji; Tonga; Rücküberweisung (Migranten); Internationale Wanderung; Einkommensverteilung; Armut; Fidschi; Tonga